2017
DOI: 10.1111/ejh.12847
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of CD5 expression in diffuse large B‐cell lymphoma in patients treated with rituximab‐EPOCH

Abstract: R-EPOCH therapy does not seem to impact the known poorer prognosis of patients with de novo CD5+ DLBCL, and CD5 expression was still an independent prognostic factor in R-EPOCH-treated patients with DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 34 publications
3
47
1
Order By: Relevance
“…Thakral et al demonstrated that CD5 expression is an independent prognostic factor in DLBCL patients treated with DA-EPOCH-R. 37 Despite the transplantations, some investigators have found that the OS of patients with CD5+ DLBCL could not be improved. [37][38][39] Studies have shown that the overexpression of CD5 in malignant B cells may confer chemo-resistance, upregulate anti-apoptotic signals and change the microenvironment. 40 Further studies are needed to clarify the causes for the poor prognosis of CD5+ DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thakral et al demonstrated that CD5 expression is an independent prognostic factor in DLBCL patients treated with DA-EPOCH-R. 37 Despite the transplantations, some investigators have found that the OS of patients with CD5+ DLBCL could not be improved. [37][38][39] Studies have shown that the overexpression of CD5 in malignant B cells may confer chemo-resistance, upregulate anti-apoptotic signals and change the microenvironment. 40 Further studies are needed to clarify the causes for the poor prognosis of CD5+ DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…CNS relapses occurred in 5.8%, without any significant difference according to the administration of intrathecal therapy. Researchers from MD Anderson Cancer Center reported a higher rate of CNS recurrence after DA-EPOCH-R in CD5+ disease (33% versus 16%), which in 50% was associated with extranodal involvement at diagnosis, most commonly in the bone marrow (35%) [47]. CD5 positivity may thus be another marker of disseminated disease with high risk of CNS recurrence, reported as 8–11% in three other series [4850].…”
Section: Cns Recurrence: Risk Assessment and Prophylaxismentioning
confidence: 99%
“…CD5 is also expressed in 5%‐10% of de novo DLBCL cases, and CD5+ DLBCL has been included as an immunohistochemical subgroup in the fourth edition of the World Health Organization (WHO) classification . Several studies have demonstrated that DLBCL patients with CD5‐positive expression have a poorer overall survival (OS) rate than those without CD5 expression, regardless of the use of rituximab …”
Section: Introductionmentioning
confidence: 99%
“…12 Several studies have demonstrated that DLBCL patients with CD5-positive expression have a poorer overall survival (OS) rate than those without CD5 expression, regardless of the use of rituximab. 23,24 CD43 is a multifunctional type I transmembrane protein that regulates multiple cellular functions, such as cell signal transduction, cell adhesion, activation, proliferation, cell survival, and apoptosis. [25][26][27] CD43 is expressed on the surface of most hematopoietic cells, some lymphomas, and leukemias.…”
mentioning
confidence: 99%